Allelopathic interference of silverleaf nightshade (Solanum elaeagnifolium Cav.) with the early growth of cotton (Gossypium hirsutum L.) - Pieterse, P.J. (University of Pretoria, 2013)
Dissertation (MSc(Agric) Agronomy (Weed Science))--University of Pretoria, 2007.